MÉTODO LOGÍSTICO PARA EL ABASTECIMIENTO DE MATERIA PRIMA EN LA EMPRESA WILPAC PARA LA FABRICACIÓN DE MAQUINARIA AGRÍCOLA - Sánchez Mera, Mark Anthony (2023)
This paper documents the result of a work dedicated to supply logistics. Focused on the logistic method applied in the Wilpac company for the supply of raw material for the manufacture of agricultural machinery. The results with the use of this method will be significant for the improvements of the supply chain. The identification of raw materials, their acquisition, storage and transportation will present a general improvement to the logistic process in the Wilpac company.